2010
DOI: 10.1017/s0007114510001078
|View full text |Cite
|
Sign up to set email alerts
|

A human volunteer study to assess the impact of confectionery sweeteners on the gut microbiota composition

Abstract: Sweeteners are being sourced to lower the energetic value of confectionery including chocolates. Some, especially non-digestible carbohydrates, may possess other benefits for human health upon their fermentation by the colonic microbiota. The present study assessed non-digestible carbohydrate sweeteners, selected for use in low-energy chocolates, for their ability to beneficially modulate faecal bacterial profiles in human volunteers. Forty volunteers consumed a test chocolate (low-energy or experimental choco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 52 publications
0
56
2
1
Order By: Relevance
“…Interestingly, bifidobacteria have shown a positive correlation with HDL-cholesterol [111], but the bifidobacterial counts were decreased by polydextrose when studied with pyrosequencing [114]. In other studies polydextrose administration has been shown to increase the amount of bifidobacteria and lactobacilli [17,18,49,106,107,115] while in some studies this effect has not been noted [103] or that there was no effect on the growth of lactobacilli [102]. This kind of inconsistency in the response could reflect the interindividual differences in indigenous microbiota to begin with.…”
Section: Role Of Polydextrose On Intestinal Microbiota and Its Impactmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, bifidobacteria have shown a positive correlation with HDL-cholesterol [111], but the bifidobacterial counts were decreased by polydextrose when studied with pyrosequencing [114]. In other studies polydextrose administration has been shown to increase the amount of bifidobacteria and lactobacilli [17,18,49,106,107,115] while in some studies this effect has not been noted [103] or that there was no effect on the growth of lactobacilli [102]. This kind of inconsistency in the response could reflect the interindividual differences in indigenous microbiota to begin with.…”
Section: Role Of Polydextrose On Intestinal Microbiota and Its Impactmentioning
confidence: 99%
“…Fecal SCFA concentration measurements are not the best indicators of SCFA produced as the majority of fecal SCFA is absorbed rapidly by the colonic epithelial cells [99]. Polydextrose has been observed to increase the production of butyrate, acetate and propionate in vitro [18,[100][101][102], in rats [20], pigs [11], in dogs [103] and in humans [17,49]. When compared to other fibers, polydextrose produced similar quantities of SCFAs, and the molecular ratio of acetate/propionate/butyrate produced was found to be similar to that of fructo-oligosaccharides and xylo-oligosaccharides and other carbohydrates, such as inulin, pectin, and arabinose [104,105] while in other studies polydextrose produced less total SCFAs compared to FOS, inulin and GOS [102,106,107].…”
Section: Role Of Polydextrose On Intestinal Microbiota and Its Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…Four randomised controlled trials were identified that presented evidence on resistant starch supplementation in relation to faecal Bifidobacterium spp. content (Jenkins et al, 1999c;Pasman et al, 2006;Fastinger et al, 2008;Beards et al, 2010). No further trials were identified in the update search (Colo-rectal health review p85).…”
Section: Faecal Bacteriamentioning
confidence: 99%
“…The data on measures of faecal bacteria content were insufficiently comparable to allow a metaanalysis. Three trials supplemented subjects with chemically modified resistant starch (RS 4 ) (Pasman et al, 2006;Fastinger et al, 2008;Beards et al, 2010), the other trials supplemented subjects with either raw resistant starch (RS 2 ) or retrograde resistant starch (RS 3 ) (Jenkins et al, 1999c …”
Section: Faecal Bacteriamentioning
confidence: 99%